Learning in times of lockdown: How Covid-19 is affecting education and food security in India - Alvi, Muzna; Gupta, Manavi (Springer, 2020)
A vast majority of the relief and rehabilitation packages announced in the months following the nationwide lockdown in India have focused on economic rehabilitation. However, the education sector has remained absent from this effort, including in India’s central government’s 250 billion dollar stimulus package. In this paper, we discuss the implications of lockdown-induced school and rural child-care center closures on education and health outcomes for the urban and rural poor. We especially focus on food and nutritional security of children who depend on school feeding and supplementary nutrition programs. We argue that the impacts are likely to be much more severe for girls as well as for children from already disadvantaged ethnic and caste groups. We also discuss ways in which existing social security programs can be leveraged and strengthened to ameliorate these impacts.